10 Tahun Kebijakan Jokowi dalam Perlindungan Pekerja Migran: Pemenuhan Hak atas Perlindungan Pekerja Migran Indonesia masih Terbatas - Wardhani, Savitri Wisnu (Jurnal Perempuan, 2024)
The migration of Indonesian migrant workers has brought positive contributions to economic development in both the countries of origin and destination of Indonesian migrant workers. In an effort to provide protection for Indonesian migrant workers, the government has issued Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers and has carried out several protection initiatives. However, cases experienced by Indonesian migrant workers for 10 years actually show a lack of protection efforts for them. Women migrant workers in the informal sector are even more vulnerable to violence. This is due to the policy perspective that is more targeted at the area of economic gain than protection. Qualitative method exploration was carried out through the collection of literature study data and compilation of policy data for Indonesian migrant workers during the 10 years of President Joko Widodo’s administration. The findings of this study indicate that there is a lack of commitment to protection efforts due to the lack of involvement of the experiences of Indonesian migrant workers in the process and implementation of policies. This study also proposes further steps that need to be taken to improve policies and implementation related to the protection of migrant workers.